The Concept of Human Rights-Based Criminal Punishment for Children Who Commit Murder - Iskandar, Ismail; Syamsuddin Muchtar; Hijrah Adyanti Mirzana; Audyna Mayasari Muin; Muhammad Hasrul; Rafika Ramli (Universitas Airlangga, 2026)
Murder committed by children is a serious crime that causes shock in society and poses a challenge to the criminal justice system. In handling such cases, the state is not only obliged to enforce the law and provide justice for the victims, but also to guarantee the protection of the human rights of the child perpetrator, in accordance with the principles of human rights (HAM). This study aims to examine the concept of sentencing children who commit murder using a human rights-based approach. The method employed is normative research, involving an analysis of national legislation, specifically the National Criminal Code and the Child Criminal Justice System Law (UU SPPA), as well as international instruments such as the Convention on the Rights of the Child. The findings indicate that although murder is classified as a serious crime, the approach to sentencing children must uphold the principles of non-discrimination, the best interests of the child, and the right to rehabilitation.